(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to explain the concept of re-evaluation and its importance, present the requirements for re-evaluation in accordance with international financial reporting standards, measure the impact of re-evaluation on the suitability and credibility of income statement information, and the descriptive analytical method was used to test the hypothesis by the researchers by analyzing the data of the oil pipeline company. The researchers reached a set of conclusions, the most prominent of which is that the revaluation was not applied to oil and gas pipelines by the Oil Pipelines Company because it did not apply international financial reporting standards, and a decrease (50%) of the net profit shown in the income statement upon revaluation from what it was before the revaluation. Evaluation, and therefore the researchers proposed several recommendations, the most important of which is the adoption and application of international financial reporting standards in the oil pipeline company, as they are standards that express cases and experiences that have appeared on the ground, and their issuance was based on agreement and consultations by several countries, and the use of the income approach in measuring oil and gas pipelines at fair value. To make income statement information more appropriate.